THE USE OF LEARNING MANAGEMENT SYSTEM ON ESP COMPUTER STUDENTS’ WRITING SKILLS DEVELOPMENT: A CASE STUDY IN INDONESIA - La Ode Sanu (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2023)
With the advancement of computer program and Internet-based technology, many higher education institutions provide Learning Management Systems (LMS) to facilitate online teaching and learning. This study was intended to explore students’ experiences during the use of the LMS of WeLearn as a tool for writing skills development. It used a case study design and involved two online classes consisting of 24 freshmen ESP computer students in a private higher education institution of Informatics and Computer Management in East Kalimantan, Indonesia. It used self-report and observation in the data collection. The findings showed that the students actively used the Welearn system to accomplish the online course. They had positive experiences and perceived the benefits on the use of the WeLearn system. The benefits were easy to use and access as well as was cost-effective. Additionally, the WeLearn system could develop students’ writing skill, linguistic competence, technology skill, high learning motivation, self-management, time management, responsibility, self-confidence, accountability, independence, and creativity. However, the students encountered some challenges such as unstable internet connection, distracted learning concentration, unenthusiastic learning interaction, absence of alert information, and writing plagiarism.